Clinical Significance of Serum Soluble TNF Receptor I/II Ratio for the Differential Diagnosis of Tumor Necrosis Factor Receptor-Associated Periodic Syndrome From Other Autoinflammatory Diseases - Yasumura, Junko; Shimizu, Masaki; Toma, Tomoko; Yashiro, Masato; Yachie, Akihiro; Okada, Satoshi (Frontiers in Immunology, 2020)
Objectives Genetic analysis of TNFRSF1A can confirm the diagnosis of tumor necrosis factor receptor-associated periodic syndrome (TRAPS), but interpretation of the pathogenesis of variants of unknown significance is sometimes required. The aim of this study was to evaluate the clinical significance of serum soluble tumor necrosis factor receptor type I (sTNFR-I)/II ratio to differentiate TRAPS from other autoinflammatory diseases. Methods Serum sTNFR-I and sTNFR-II levels were measured using an enzyme-linked immunosorbent assay in patients with TRAPS (n=5), familial Mediterranean fever (FMF) (n=14), systemic juvenile idiopathic arthritis (s-JIA) (n=90), and Kawasaki disease (KD) (n=37) in the active and inactive phase, along with healthy controls (HCs) (n=18). Results In the active phase, the serum sTNFR-I/II ratio in patients with s-JIA, KD, and FMF was significantly elevated compared with that in HCs, whereas it was not elevated in patients with TRAPS. In the inactive phase, the serum sTNFR-I/II ratio in patients with s-JIA and FMF was significantly higher compared with that in HCs, and the ratio was lower in TRAPS patients than in patients with s-JIA and FMF. Conclusions Low serum sTNFR-I/II ratio in the active and inactive phase might be useful for the differential diagnosis of TRAPS and other autoinflammatory diseases.